Flexible Nanogenerators: Flexible Transparent Nanogenerators Utilizing Shape‐Modulated ZnO Nanorod Arrays on Graphene Electrodes (Adv. Mater. Technol. 4/2018). Issue 4 (17th April 2018) - Son, Myungwoo; Jang, Hanbyeol; Lee, Mi‐So; Yoon, Tae‐Ho; Lee, Byoung Hun; Lee, Woong; Ham, Moon‐Ho
Abstract : In article number1700355, Woong Lee, Moon‐Ho Ham, and co‐workers demonstrate flexible and transparent hybrid piezoelectric nanogenerators based on vertically aligned, shape‐modulated ZnO nanorod arrays and graphene electrodes for self‐powered wearable electronics. These devices are developed using a simple stamping transfer method on flexible substrates. The largest piezoelectric power generation is obtained for Cd‐doped ZnO nanorods having a very low aspect ratio.